Antioxidant Activity, Cytotoxicity, and Identification of Secondary Metabolites of Kigelia africana from Waterpark Platinum Riau - Fitri, Iis Yusma; Kurniawanti, Kurniawanti; Syahbirin, Gustini; Sugita, Purwantiningsih (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Antioxidants can prevent reactive oxygen-associated diseases, which trigger carcinogenesis, cardiovascular disease, and premature aging. India and Africa have mostly practiced sausage trees (Kigelia africana) as traditional medicine, whereas Indonesia is still limited. The research aims to determine the phytochemistry and bioactivity of the n-hexane fractions from crude methanol extract of the leaves and bark of the sausage tree as antioxidants and their toxicity. The sausage tree is derived from Waterpark Platinum Riau. The sausage trees were macerated with methanol and fractionated by n-hexane and ethyl acetate. All samples were tested for their antioxidant to 1,1-diphenyl-2-picrylhydrazyl (DPPH) and cytotoxicity to Artemia salina Leach larvae. Phytochemical results of methanol crude extract, n-hexane, and ethyl acetate fractions of leaves and sausage bark showed the presence of all secondary metabolites except alkaloids in the n-hexane fraction. Antioxidant and cytotoxic activity of stem and leaf bark ethyl acetate fraction was stronger than crude methanol extract and n-hexane fraction. Based on LC-MS/MS data, the secondary metabolite components that have contributed strongly antioxidant activity of this study are flavonoid compounds such as kaempferol and the derivatives, lignans (cubebin), and steroids (pregnant).